Experimental Study on the Seismic Performance of Improved Grouted Corrugated Duct Connection (GCDC) Design for Precast Concrete Bridge Column. Issue 5 (4th April 2022) - Wang, Zhiqiang; Wu, Chengjun; Li, Tiantian; Xiao, Wei; Wei, Hongyi; Qu, Hongya
ABSTRACT: This study introduced a new design of the grouted corrugated duct connection (GCDC), which improves the structure integrity, bond strength and ease of constructability. A two-phase experimental program was performed to fully understand the connection behaviour. Phase I focused on the pull-out tests of 32 specimens in two batches with various conditions. It indicates that a connection length of 30 times of the rebar diameters would guarantee the bond strength. Phase II compared the 1/3-scale precast bridge column with its cast-in-place reference via quasi-static cyclic test. It showed that the precast column behaved similarly to that of the CIP column.